1988
DOI: 10.1523/jneurosci.08-02-00715.1988
|View full text |Cite
|
Sign up to set email alerts
|

K-252a: a specific inhibitor of the action of nerve growth factor on PC 12 cells

Abstract: K-252a, a kinase inhibitor isolated from the culture broth of Nocardiopsis sp., selectively inhibits the actions of nerve growth factor (NGF) on PC 12 cells. At a concentration of 200 nM, K-252a prevents neurite generation initiated by NGF, but not neurite generation produced by fibroblast growth factor or outgrowth produced by dibutyryl cAMP. K-252a also inhibits the induction of ornithine decarboxylase by NGF, but stimulates ornithine decarboxylase induction by epidermal growth factor. Stimulation of phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
207
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(225 citation statements)
references
References 37 publications
16
207
0
2
Order By: Relevance
“…For example it reversibly and selectively inhibited the NGF-induced morphological transformations of proliferating PC12 cells, whereas similar effects of EGF and bFGF were not blocked (Matsuda and Fukuda, 1988;Koizumi et al, 1988). Furthermore, treatment with 100 nM K252a resulted in reversion of the phenotype of Trktransformed rodent fibroblasts (Tapley et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example it reversibly and selectively inhibited the NGF-induced morphological transformations of proliferating PC12 cells, whereas similar effects of EGF and bFGF were not blocked (Matsuda and Fukuda, 1988;Koizumi et al, 1988). Furthermore, treatment with 100 nM K252a resulted in reversion of the phenotype of Trktransformed rodent fibroblasts (Tapley et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of functional insulation between the two respective signaling pathways remains equivocal. The NGF-and cAMP-dependent pathways for differentiation have been shown to be readily pharmacologically dissociable (15,16), and NGF-induced differentiation of PC12 cells does not appear to require PKA (14). On the other hand, crosstalk between the NGF and cAMP differentiation pathways has been reported (17).…”
mentioning
confidence: 99%
“…KT5926, however, seems distinct in site of action from such agents. For instance, our data show that KT5926 clearly contrasts with K-252a (Kntisel and Hefti, 1992), which blocks all actions of NGF (Koizumi et al, 1988) and appears to do so by selectively inhibiting the tyrosine kinase activity of the gp140pr010"k NGF receptor (Berg et al, 1992;Nye et al, 1992). KT5926 is also distinct from 5'-S-methyl adenosine, which blocks all NGF responses (Seeley et al, 1984).…”
Section: Mechanistic Considerationsmentioning
confidence: 85%
“…K-252a was initially defined in vitro as a selective protein kinase C inhibitor (Kase et al, 1986) but, as noted above, was subsequently shown to inhibit gp140pr010trk tyrosine kinase activity in intact cells (Berg et al, 1992;Nye et al, 1992). Finally, like K-252a (Koizumi et al, 1988) and a structurally similar compound, staurosporine (Hashimoto and Hagino, 1989) KT5926 does not exert an inhibitory effect on basic fibroblast growth factor-induced neurite outgrowth from PC1 2 or PC12-C4 1 cells. Taken together, our results suggest that KT5926 may suppress NGF-regulated neurite outgrowth via inhibition of a hitherto unidentified protein kinase.…”
Section: Mechanistic Considerationsmentioning
confidence: 93%
See 1 more Smart Citation